First Mid-infrared Detection and Modeling of a Flare from Sgr A* - Sebastiano D. von Fellenberg; Tamojeet Roychowdhury; Joseph M. Michail; Zach Sumners; Grace Sanger-Johnson; Giovanni G. Fazio; Daryl Haggard; Joseph L. Hora; Alexander Philippov; Bart Ripperda; Howard A. Smith; S. P. Willner; et al. (The Astrophysical Journal Letters)
The time-variable emission from the accretion flow of Sgr A*, the supermassive black hole at the Galactic center, has long been examined in the radio-to-millimeter, near-infrared (NIR), and X-ray regimes of the electromagnetic spectrum. However, until now, sensitivity and angular resolution have been insufficient in the crucial mid-infrared (MIR) regime. The MIRI instrument on JWST has changed that, and we report the first MIR detection of Sgr A*. The detection was during a flare that lasted about 40 minutes, a duration similar to NIR and X-ray flares, and the source's spectral index steepened as the flare ended. The steepening suggests that synchrotron cooling is an important process for Sgr A*'s variability and implies magnetic fields strengths ~ 40–70 G in the emission zone. Observations at 1.3 mm with the Submillimeter Array revealed a counterpart flare lagging the MIR flare by ≈10 minutes. The observations can be self-consistently explained as synchrotron radiation from a single population of gradually cooling high-energy electrons accelerated through (a combination of) magnetic reconnection and/or magnetized turbulence.